Renal impairment and use of nephrotoxic agents in patients with multiple myeloma in the clinical practice setting in the United States. (14th June 2017) - Qian, Yi; Bhowmik, Debajyoti; Bond, Christopher; Wang, Steven; Colman, Sam; Hernandez, Rohini K.; Cheng, Paul; Intorcia, Michele
Abstract: Renal impairment is a common complication of multiple myeloma and deterioration in renal function or renal failure may complicate clinical management. This retrospective study in patients with multiple myeloma using an electronic medical records database was designed to estimate the prevalence of renal impairment (single occurrence of estimated glomerular filtration rate [eGFR] <60 mL/min per 1.73 m 2 on or after multiple myeloma diagnosis) and chronic kidney disease (at least two eGFR values <60 mL/min per 1.73 m 2 after multiple myeloma diagnosis that had been measured at least 90 days apart), and to describe the use of nephrotoxic agents. Eligible patients had a first diagnosis of multiple myeloma (ICD‐9CM: 203.0x) between January 1, 2012 and March 31, 2015 with no prior diagnoses in the previous 6 months. Of 12, 370 eligible patients, the prevalence of both renal impairment and chronic kidney disease during the follow‐up period was high (61% and 50%, respectively), and developed rapidly following the diagnosis of multiple myeloma (6‐month prevalence of 47% and 27%, respectively). Eighty percent of patients with renal impairment developed chronic kidney disease over the follow‐up period, demonstrating a continuing course of declining kidney function after multiple myeloma diagnosis. Approximately 40% of patients with renal impairment or chronic kidney disease received nephrotoxic agents, the majority of which were bisphosphonates. As renal dysfunction may impact the clinical management of multiple myeloma and is associated with poor prognosis, the preservation of renal function is critical, warranting non‐nephrotoxic alternatives where possible in managing this population. Abstract : In this observational study, the prevalence of both renal impairment and chronic kidney disease was high in patients with multiple myeloma, affecting 61% and 50%, respectively, of patients in the OSCER cancer database in the US for the period 2012 to 2015. The onset of renal impairment was rapid after the multiple myeloma diagnosis; however, 40% of these patients nevertheless received concomitant nephrotoxic agents, most of which were intravenous bisphosphonates. As renal impairment is associated with reduced survival and may affect clinical management, preservation of renal function is critical, and non‐nephrotoxic alternatives are warranted where possible in managing the multiple myeloma population.